(untitled) (Iranian Journal of Kidney Diseases, 2014)
Immunoglobulin A (IgA) nephropathy (IgAN) is the most common form of primary glomerulopathy worldwide. Various investigations have addressed the clinical and morphological risk factors related to the risk of progression. Recently, much attention has been made toward the prognostic implication of serum uric acid in patients with IgAN. It has been observed that treatment of hyperuricemia with allopurinol in chronic kidney failure has resulted in a fall in blood pressure and inhibition of the progression of kidney injury. Recent studies have documented that hyperuricemia is an independent risk factor for IgAN, and appropriate treatment by allopurinol is a reasonable modality in these patient. We believe that allopurinol should routinely be included to the treatment of IgAN patients; however, this hypothesis requires further investigation. Clinical studies are suggested to better understand kidney protective properties of allopurinol in IgAN.